(untitled) (Terr@ Plural, 2020)
The current rural conflicts are the result of a historical process of deterritorialization and exclusion, intensified from the advance of capitalism over agriculture. Socio-territorial movements, such as the MST, challenge hegemonic power and contest the legality of capitalist property, mobilizing peasants to occupy lands that do not carry out their social function, transforming them into agrarian reform territories in Paraná. The present work, supported by field data and bibliographical references, aims to study the relationship between colonization, territorial transformations and rural conflicts, taking as reference the municipality of Barbosa Ferraz, in the state’s Midwestern mesoregion.